Analisis Pengaruh Risiko di dalam E-Commerce: Kenyamanan, Harga, Waktu, Kualitas, Kemudahan, dan Keamanan - , GISELLA YURISDA RARASSARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is motivated by the emergence of the phenomenon of online shopping through an online shop or from social networks. In particular, this study reviewed the online shopping through buying and selling in web or electronic commerce. The development of internet users push the existence of a large potential for the creation of online shopping, online shopping is now a lifestyle of modern society and reach all layers and areas, online shopping has a positive impact also for the equalization of goods distribution. The purpose of this study was to identify the risks regarding the influence of Perceived Risk in the Context of Transaction (PRT), Perceived Risk with Product/Service (PRP), Perceived Enjoyment (PE), Perceived Ease of Use (PEU), Perceived Usefulness (PU), on Purchasing Behavior (PB). This study uses primary data by giving digital questionnaires to 200 respondents which has been cosumers of shopping online. Data were analyzed by Structural Equation Model (SEM) using AMOS 19